2002
DOI: 10.1007/s00268-002-6411-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical examination is an inaccurate predictor of intraabdominal pressure

Abstract: This study was designed to establish if clinical examination can accurately predict intraabdominal pressure (IAP). Between August 1998 and March 2000 a prospective blinded observational study of postoperative intensive care unit patients was undertaken at a major trauma center. IAP was measured using an intravesicular technique and compared with clinical evaluation. An IAP of at least 18 mmHg was considered elevated. The sensitivity, specificity, positive predicative value (ppv), negative predictive value (npv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
95
1
14

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 235 publications
(111 citation statements)
references
References 26 publications
1
95
1
14
Order By: Relevance
“…A laparotomia descompressiva é considerada o único tratamento definitivo, sendo atualmente defendida também a utiliza-ção de estratégias medicamentosas na prevenção das disfunções ou falências de órgãos, com utilização principalmente de diuréticos e colóides (Sugrue et al 2002, Tiwari et al 2002, Cheatham et al 2007.…”
Section: Introductionunclassified
“…A laparotomia descompressiva é considerada o único tratamento definitivo, sendo atualmente defendida também a utiliza-ção de estratégias medicamentosas na prevenção das disfunções ou falências de órgãos, com utilização principalmente de diuréticos e colóides (Sugrue et al 2002, Tiwari et al 2002, Cheatham et al 2007.…”
Section: Introductionunclassified
“…More recently, Soler Morejon et al identified the importance of the zero reference level and its impact on IAP measurement in surgical patients after abdominal surgery [17]. A clinical examination is not a reliable indicator of IAP [18,19]. The abdominal perimeter also correlates poorly with IAP [20].…”
Section: Factors Affecting Iap Measurementmentioning
confidence: 99%
“…Physical examination has little importance in the detection of IAH and it is a poor predictor of ACS [7,23]. Imaging with chest radiography to recognize decreased lung volumes, atelectasis or elevated hemi diaphragms, or the use of computed tomography (CT) to detect infiltration differences between the retroperitoneal and peritoneal cavity or extrinsic compression of the inferior vena cava or abdominal distension, are also not helpful in the diagnosis of ACS [24,25].…”
Section: Iap Measurementmentioning
confidence: 99%